The Acculturation of Former Yugoslavian Refugees - Djuraskovic, Ivana; Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2009)
Although the displacement of people from their home countries is of growing concern, little attention has been paid to refugees in the counselling literature. Experiences of refugees are more complex and difficult than those of voluntary immigrants because refugees are typically pushed out of their countries. Using heuristic inquiry, four main categories of themes characterized acculturation and identity reconstruction experiences for six individuals from the former Yugoslavia. These categories suggest that the acculturation and identity reconstruction are multifaceted and lifelong processes for refugees. Suggestions for counselling personnel who work with refugees are discussed.